Utilization of E-waste & Marble Waste Slurry in Production of Tuff Tile for Sustainable Environment - Syed Muhammad Shakir Bukhari; Rehman Akhtar; Feroz Shah (Indus Journal of Social Sciences, 2025)
E-waste and the waste slurry from marble are now a significant environmental and disposal concern everywhere. It reviews the process of producing tuff tiles using recycled waste materials which are important for the construction industry. The intention of the project is to cut down pollution by replacing common ingredients in tiles—fine aggregates and cement—with marble slurry and e-waste plastics, but still keep the structure and function of the tiles. All main factors such as compressive strength, flexural strength, water absorption, abrasion resistance, density, thermal conductivity and the carbon footprint reduction are analyzed through a meta-analysis of experimental evidence. It was found that mixing up to 10% e-waste with 25% marble slurry brings the best results. Discarded electronics reduce the weight of tiles and enhance thermal comfort and marble slurry increases the strength and smoothness of tiles due to having fine particles and fillers. The main environmental gain is a 30% drop in CO₂ emissions, mainly because of the replacement of cement and natural aggregates. Using industrial waste lessens manufacturing costs and supports a circular economy. From the research it is evident that using both e-waste and marble slurry in tuff tile making is technically possible, supports sustainability and is good for business. It shows the potential for more waste materials to be used in construction, encouraging new sustainable construction ideas. More studies should be done in the areas of field use, long-term performance checks and standardized ways to design concrete mixes. Creating tuff tiles from these wastes lessens major environmental issues and also promotes sustainability and waste management around the world.